VLE Moodle personalization using Web 2.0 tools - Juškevičienė, Anita; Kurilovas, Eugenijus (Lietuvos matematikos rinkinys, 2012)
The goal of this paper is to determine whether the VLE Moodle 2.2 is a sufficient for successful learning inresponse to appropriate learning activities suitable to particular learning style. The survey showed that the majorityof these tools are applied in Moodle. The problem is that it is quite difficult for the learner to identify all these tools while working in VLE, and use them in a proper way. Therefore, it is recommended to constructand install semanticsearch engine for learning toolsinto VLE. The engine will facilitate the search processby optimizing workloads, thereby improving learner’s satisfaction and improving the efficiency andeffectiveness of the learning process.
Keywords: Web 2.0; semanticsearch; VLE; learningstyle